Pengaruh Penggunaan Bahan Perekat Tepung Sagu, Tapioka, dan Beras Terhadap Daya Bakar Briket Tempurung Kelapa - Junardi; Febrina, Asti; Kartika, Yuni (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
The need for energy is increasing as the population grows. Efforts to produce alternative energy continue. One of them is by utilizing materials that are more environmentally friendly, more economical, and easily obtained. Therefore, the utilization of coconut sells in briquettes is one of the alternative fuels for energy fulfillment. The use of this material is also a form of handling coconut waste that has not been optimally utilized. The method used in making this briquette is by combining it with various types of adhesives such as sago flour, tapioca and rice with various variations in the on combustibility, moisture content, and shatter index. Variations in the amount of adhesive used were 6%, 8% and 10%. Drying of the briquettes was carried out in an oven with temperatures of 60Â°C. The results showed that the best briquettes in the 60Â°C drying temperature treatment had a combustibility value of 0.0300 gr/min with 10% sago adhesive. Moisture content is 3.8314% with 6% rice adhesive. Shatter index with a value of 0.0763% with 8% rice adhesive.